Strict U-Ideals and U-Summands in Banach Spaces
For a strict u-ideal X in a Banach space Y we show that the set of points in the dual unit ball B_X^* , strongly exposed by points in the range TY of the unconditional extension operator T from Y into the bidual X^** of X, is contained in the weak^* denting points in B_X^* . We also prove that a u-embedded space is a u-summand if and only if it contains no copy of c_0 if and only if it is weakly sequentially complete. , number=2, journal=MATHEMATICA SCANDINAVICA, author=Abrahamsen, Trond A., year=2014, month=May, pages=216–225